A Values-Based Strategic Decision-Making Model in Community Islamic Educational Institutions: A Case Study of SD Islam Al Ittihad - Erwin Novriyanto; Heny Suharyati (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to develop a values-based strategic decision-making model within community-based Islamic educational institutions. Using SD Islam Al Ittihad as a case study, this research explores how Islamic values can guide institutional decisions to sustain educational quality without external debt. The research employs a qualitative case study approach with data collection through interviews, observation, and documentation. Data were analyzed using a triangulation method and supported by SWOT analysis through EFAS and IFAS matrices. The strategic decision-making process was further examined using Mintzberg's and Kepner-Tregoe's frameworks. The findings show that decision-making grounded in Islamic values enables educational institutions to achieve sustainability through strategic intuition, leadership commitment, and value-based planning. This research contributes a conceptual framework for Islamic educational leaders and policymakers seeking to integrate faith-driven values in governance and strategic planning. Further studies are suggested to test this model across various community-based schools to assess its broader applicability.